PENGARUH DOSIS PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (ORYZA SATIVA L.) VARIETAS CIHERANG PADA SISTEM LEGOWO 4 - Asep Ikhsan Gumelar (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
A field experiment to study the effect of urea fertilizer on the growth and yield of rice varieties Ciherang Legowo system 4. The experiment was conducted from October 2013 to January 2014 . Held in the Village District of Dawuan Manyeti Subang district , with an altitude of 300-500 meters above sea level. The type of soil with a pH of 4.7 is Alvulial precipitation type including classification into type B according to Schmidt and Ferguson (1951). The design used was a randomized block design consisting of a single factor, namely Urea Dosing consisted of 6 level : A = Without Urea, Urea Dosing, B = 100 kg/ha, C = Dose Urea 150 kg/ha, D = dose of fertilizer urea 200 kg/ha, E = Dose urea 250 kg/ha and F = Dose urea 300 kg/ha. The experimental results showed, Effect of Urea Dosing occurs on the growth and yield of rice varieties Ciherang Legowo system 4, dose Treatment of Urea 250 kg/ha gave the best results, urea fertilizer application of 250 kg/ha of dry grain harvest weight generating an average of 6.74 kg/plot, the means of production is 6.74 tons a hectare.